Analysis of the takeoff motion for the world top female triple jumpers - Tsukuno, A.; Ae, M.; Koyama, H.; Muraki, Y.; Takamoto, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to investigate the characteristics of the takeoff motion for world-top female triple jumpers by comparing with Japanese university male triple jumpers who have equivalent marks in the triple jump. The subjects were five world top female Jumpers (WF) and four male Jumpers (JM). The motions of the three takeoff phases were videotaped and analyzed (2D motion analysis). The results were as follows; the horizontal CG velocity for WF changed less than that of the JM, implying less braking. WF was characterized by shorter landing distance, forward-leaning trunk and the extended knee joint of the takeoff leg, which may have allowed WF to maintain the horizontal CG velocity and to exert greater leg extension force during the takeoff.